The crystal structure of (2-(4-chlorophenyl)-5-methyl-1,3-dioxan-5-yl)methanol, C12H15ClO3 - Zou Long-Sheng; Li Zhong-Yan; Yuan Lin (Zeitschrift für Kristallographie - New Crystal Structures)
C12H15ClO3, orthorhombic, P212121 (no. 19), a = 5.788(2) Å, b = 11.079(4) Å, c = 18.916(7) Å, V = 1213.0(8) Å3, Z = 4, Rgt(F) = 0.0559, wRref(F2) = 0.1898, T = 296(2) K.